Features of hair structure of women which born prematurely and their babies. - Shkolna, I. I.; Markevych, V. E. (Морфологія / Morphologia / Morfologìâ, 2017)
Background. Prematurity is one of the most important problems of modern perinatology and pediatrics. Objective. The aim of study was to investigate the structural characteristics of hair of mothers and their premature babies. Methods. We studied hair of 40 mothers and their newborn babies (30 mothers and their premature infants and 10 mothers which born healthy term infants). Material for study were collected in the first day after birth. Studying hair morphological characteristics was performed using scanning electron microscopy. Results. Hair diameter of preterm infants depended on gestational age, while their mothers - hair thickness was greater in those which born at a later period of gestation. Hair of women which born prematurely had structural changes: deformation of the surface, presence of gaps, fissures and cracks, thinning of the horny scales. Moreover, presence of above changes in hair depended on gestational period of preterm labor – as bigger it was less significant changes we saw. Hair of premature newborns also had structural features: picture of cuticle visualized bad. We saw sharp jagged edges, cracks and on fissures on its surface. As bigger term of gestation it was less pronounced changes we found. Conclusion. Gestational age associated with deformation of the edges, scales, fissures, cracks and gaps on the surface of preterm infant’s hair and their mothers. As greater gestation period it was less pronounced changes in the mothers and babies we found. The thickness of baby’s hair increased with increasing of gestational age.